Gestão democrática e gerencialismo a percepção dos diretores das escolas estaduais da coordenação regional de Goiânia estudo de caso - Alves, Elisane Silva (2024)
The research entitled - Democratic Management and Managerialism the perception of directors of state schools of the Regional Coordination of Goiânia case study, aims to understand how management in schools starts to be conceived, from 2011, with the incorporation of the new managerialism present in the guidelines of Pact for Education in Goiás directing educational reform in the state network. The research analyzes how the principles of NGP, inserted in the state education network of Goiás, guided the management of schools with administrative and ideological values of private management based on performance, meritocracy and accountability, implying the work of the director and giving new meaning the mechanisms for implementing democratic management. It is important to understand how the principals, operational subjects of the school organization, perceived the set of changes underway and what the main effects are on management practice and the work collective. To this end, this research aims to: i) identify how the principles of NPM relate to education and school management; ii) examine how democratic management is conceived in schools; iii) analyze how the Goiana Education Pact restructured management in schools; and, iv) understand how the directors of state schools in the Regional Coordination of Goiânia perceived the insertion of managerialism in school management and its relationship with democratic management. This research has theoretical support from Andrade (2019); Andrade, Côrtes and Almeida (2021); Newman and Clarke (2012); Verger and Normand (2015); Oliveira (2015); Dasso Júnior (2014); Libâneo (2001; 2011; 2018); Paro (1987; 2010; 2012); Cury (2002; 2007); Ferreira (2004); Sanders (2009); Silva (2014); Silva (2005); Marques (2020); Silva and Teixeira (2019; 2022); Afonso (2013); Barroso (2005; 1998; 1998; 2011); Souza (2003; 2009); Lima (2014; 2018; 2019). To achieve the established objectives, the qualitative approach was used as a methodology from the perspective of Minayo (2001; 2012), Godoy (1995) and Duarte (2002), constructed by bibliographical research, referenced in Sousa, Oliveira and Alves (2021); documentary analysis Duarte (2002), content analysis described in Bardin (1977); Moraes (1999); and, a multiple case study in Ventura (2007); Pereira; Costa (2008) through semi-structured interviews, Frazer; Gondim (2004) with a purposive or intentional sample that is guided by pre-defined criteria when choosing the participant's profile. For this, the specificities between them were considered, in this case, directors of five schools in the state education network of Goiás with a focus on the Regional Coordination of Goiânia. The selection criteria for research subjects are: a) time and experience in school management; b) geographic location of the school; c) school standard; d) teaching modality. To analyze the interviews, a content analysis was developed with the intention of understanding how the incorporation of managerialism and the consequences of the actions of the Pact for Education since 2011 have interfered in the management of schools and the implementation of democratic management. The research indicated the alignment of educational policies implemented in the state education network of Goiás following the Guidelines of the Pact for Education with the principles of NGP and the deepening of the logic of management focused on results with external evaluations and the submission of the director/ to meritocratic, evaluative and accountability policies. The discourse on the principals' conception of management pointed to the perspective of democratic management, approaching the idea of participation and collective construction of actions at school. However, we note that conservative practices still persist, still centered on the figure of the director and democratic management of results.